Silence as a Coping Strategy: Non-Disclosure of Sickle Cell Disease and its Psychosocial Consequences for Families in Urban Cameroon: An Analytical Cross-Sectional Study - Wankam, Mispar Guinyonga; Pangna , Kouotou Ibrahim Cherif; Mtsavara , Joseph; Enjeh, Carine Ngah; Yembeau , Lena Natacha; Kengne , Djeudjo Ingrid Fabiola (International Journal of Health Sciences, 2026)
Purpose: This analytical cross-sectional study evaluated the occurrence of non-disclosure and its psychosocial effects among 184 families in two pediatric units in Yaoundé-Cameroon. Methodology: Predefined questionnaires evaluated disclosure behaviors, stigma perception, emotional distress, family bonding, and social support. Data analysis was done using descriptive statistics, Pearson correlations, and linear regressions. Findings: Findings indicated that participants (63.6%) do not disclose information partially or completely and non-disclosure had a positive relationship with stigma perception (r = 0.50) and emotional distress (r = 0.40), a negative relationship with family bonding (r = −0.38) and social support (r = −0.30), acting as an independent predictor of psychological distress (β = 0.34). Silence protects against stigma but creates negative social and psychological impacts, demonstrating the need for stigma prevention measures and disclosure assistance. Unique Contribution to Theory, policy, and Practice: The results of this research indicate that stigma, communication, and psychological outcomes in families with sickle cell disease are related to one another. And, further to that, the data provides information on what to do in terms of policy and the need for reducing stigma through the provision of psychosocial support and the development of guidance for healthcare providers about disclosing sickle cell disease. Lastly, the practice as nurses emphasizes the need for recognizing silence as a sign of vulnerability and delivering culturally competent, family-centered nursing to families impacted by sickle cell disease.